Wajda mowi o sobie : wywiady i teksty - Wajda, Andrzej, 1926-; Wertenstein, Wanda (Krakow : Wydawn. Literackie, 1991)
Conversations and interviews with Wajda by various journalists. This is a quasi biography and study of films and directing in Poland.
Includes bibliographical references, filmography, and indexes.
Keywords: Wajda, Andrzej, -- 1926-; Motion pictures -- Poland; Theater -- Poland